Optimisation mechanism for web search results using topic knowledge. (5th May 2006) - Panagis, Yannis; Sakkopoulos, Evangelos; Garofalakis, John; Tsakalidis, Athanasios
Web searching – one of the most frequent activities in the internet community – is perhaps the most complicated one because of the abundant resulting information available. Users are often puzzled because of long results of ranking lists that are compiled without considering their individual preferences and needs. We present a mechanism in this work that reranks and groups search results on the user's side according to his/her explicit and implicit choices. Furthermore, a caching strategy is introduced to minimise personalisation effect response time. A web environment prototype has been developed to exemplify the potentials of the proposed mechanism. User assessment has been conducted to verify the effectiveness of the mechanism. Results and feedbacks have been efficient and encouraging, respectively.